Analyzing Open Access Impact to Learning Spaces - Crumpton, Michael (Qualitative and Quantitative Methods in Libraries; Vol 9 No 4 (2020): December Issue 2020, 2021)
Abstract:  This paper will give an overview of the inception of open access journal production and support at The University of North Carolina at Greensboro, with a focus on the Journal of Learning Spaces . The journal brings together editorial board members and authors from academic departments, university libraries, teaching and learning centers, student affairs offices, information technology units, and related groups at academic and research institutions around the country and across the world, with the common goal of developing, sharing, and enriching the scholarship of learning spaces. The paper will also discuss roles and skills needed for journal success, challenges involved in the creation of open access resources, and benefits to both hosting institutions and the broader communities of participants and readers.